2008
DOI: 10.3200/jmbr.40.4.301-314
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Relationship Between Movement Velocity and Movement Distance in Primary Focal Hand Dystonia

Abstract: The authors examined the relationship between movement velocity and distance and the associated muscle activation patterns in 18 individuals with focal hand dystonia (FHD) compared with a control group of 18 individuals with no known neuromuscular condition. Participants performed targeted voluntary wrist and elbow flexion movements as fast as possible across 5 movement distances. Individuals with FHD were slower than controls across all distances, and this difference was accentuated for longer movements. Musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
9
1
Order By: Relevance
“…Moreover, we found no significant group difference in terms of the quality of the movement, i.e., straightness, smoothness and overshooting. Our kinematic results are in contrast to those of previous studies showing the slowness of movement in patients with dystonia (Agostino et al, 1992; Curra et al, 2000; Prodoehl et al, 2008). Differences in results, however, may reflect the different movements analysed or the clinical heterogeneity of patients enrolled in the various studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, we found no significant group difference in terms of the quality of the movement, i.e., straightness, smoothness and overshooting. Our kinematic results are in contrast to those of previous studies showing the slowness of movement in patients with dystonia (Agostino et al, 1992; Curra et al, 2000; Prodoehl et al, 2008). Differences in results, however, may reflect the different movements analysed or the clinical heterogeneity of patients enrolled in the various studies.…”
Section: Discussioncontrasting
confidence: 99%
“…This algorithm has been used during movement (Vaillancourt et al 2004; Prodoehl et al 2008) and force production tasks (Prodoehl et al 2006). …”
Section: Methodsmentioning
confidence: 99%
“…Co-contraction activity between agonist and antagonist muscles may have a detrimental effect on the execution of voluntary movement, for example, in FHD patients performing the task triggering cramps [21,70]. Bradykinesia in dystonia, however, has also been demon- between antagonist muscle groups cannot be clearly identified [71], as well as in non-dystonic body segments, that is, where there is no co-contraction activity. Weakness and increased muscle tone may also potentially explain the presence of bradykinesia in patients with ALS, primary lateral sclerosis, stroke, and MS [132,137,139,187], although studies specifically addressing this issue are lacking.…”
Section: Role Of Secondary Factorsmentioning
confidence: 99%
“…Neurophysiological investigations in patients with generalized dystonia and FHD have variably shown that movement preparation can be abnormally prolonged [52][53][54][55][56][57][58][59][60]63,67,69]. Kinematic and electromyographic (EMG) recordings have demonstrated that in comparison with healthy subjects, patients performed single and multijoint arm movements with slower velocity and reduced amplitude, with co-contraction of agonist and antagonist muscles [21,65,70] or reduced contraction of muscle activity [66,71]. Bradykinesia has also been observed during reaching arm movements in patients with idiopathic torsion dystonia [61] or during sequential arm movements and finger-tapping in patients with generalized dystonia and FHD [6,62,[72][73][74], although these results are not always consistent [75][76][77] and no studies have specifically investigated sequence effect in dystonic patients.…”
Section: B R Adykine S Ia In Hyperkine Tic Movement Disorder S Dystoniamentioning
confidence: 99%